Binary high-nickel single-crystal lithium ion battery positive electrode material as well as preparation method and application thereof
By adopting the three-element doping method of dual main elements and one sub-element in the positive electrode material of binary high-nickel single crystal lithium-ion battery, the problem of insufficient circulation performance of the material under high temperature conditions is solved, and the high-temperature circulation performance is significantly improved and capacity maintenance is achieved.
Patent Information
- Application Number
- CN202411710076.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
AI Technical Summary
The existing binary high-nickel single crystal lithium-ion battery positive electrode material has poor circulation performance under high temperature conditions, which limits its application in battery systems.
The three-element doping method of double main elements and one sub-element is adopted. By selecting Z ions with an ion radius close to nickel ions and X ions with an ion radius greater than nickel cobalt ions, a stable metal oxygen bond is formed, reducing the generation of oxygen vacancies, and providing electron-stable oxygen ion valence state through covalent bonding, thereby improving high-temperature cycling performance.
The high-temperature cycling performance of the positive electrode material of binary high-nickel single crystal lithium-ion battery is significantly improved, while maintaining high capacity performance, ensuring the stability and efficiency of the material under high temperature conditions.
Smart Images

Figure CN119517963A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a binary high-nickel single crystal lithium ion battery positive electrode material and a preparation method and application thereof. Background Art In the context of vigorously promoting the development of electric vehicles, lithium-ion batteries need to further improve energy density and reduce costs in order to obtain electric vehicles that can match the endurance performance and price of fuel vehicles. This has further promoted the development of high-nickel single crystal materials with Ni content > 90%. However, as the nickel content increases, the material deteriorates more obviously, the capacity cannot continue to increase, and the cycle performance also decreases rapidly. Ultra-high nickel single crystals can alleviate the problem of rapid cycle attenuation to a certain extent, but still cannot meet market requirements. Therefore, how to increase the capacity of ultra-high nickel single crystal materials and improve their high-temperature cycle performance without reducing the capacity is the current primary issue, and it is also the main factor restricting the marketization of ultra-high nickel single crystals.
[0002] The patent with announcement number CN114068912 B discloses a binary high-nickel single crystal positive electrode material and its preparation method, a binary high-nickel single crystal positive electrode material, whose primary particle size is 1.1-1.8 μm and secondary particle size D50 is 3.0-8.0 μm. Its preparation method comprises: mixing the nickel-cobalt binary precursor, lithium source, and a first additive containing element X according to the stoichiometric ratio, and then sintering, mixing the sintered product with the second additive containing element M, and then sintering to obtain a binary high-nickel single crystal positive electrode material. During the battery charging and discharging process, the above-mentioned binary high-nickel single crystal positive electrode material has a new discharge platform between 3.4 and 3.5V, so that it has a high first efficiency and high discharge capacity that are difficult to achieve with conventional ternary single crystals. However, the high-temperature cycle performance of binary single crystals is poor, which limits its application in battery systems.
[0003] The crystal structure and chemical properties of binary single crystals are quite different from those of traditional NCM materials. Since the ion radius of Ni and Co is close to that of Li, Ni ions easily enter the Li layer during the cycle, resulting in cycle attenuation. In ternary materials, Mn ions occupy the Ni position and have a larger ion radius, which prevents Ni ions from entering the Li layer. Therefore, the high-temperature cycle of binary single crystal materials is worse. The modification effects of the two systems are not similar. The modification schemes of traditional ternary materials are often difficult to achieve the expected results when applied to binary materials. For example, doping with Sb and Nb elements can improve the high-temperature cycle performance of NCM materials, but its application to binary high-nickel single crystals has almost no effect. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a binary high-nickel single crystal lithium ion battery positive electrode material with good high temperature cycle performance and its preparation method and application. In order to solve the above technical problems, the technical solution proposed by the present invention is: a binary high-nickel single crystal lithium ion battery positive electrode material, whose chemical formula is Li x Ni a Co b X c Z d M p A n O f , wherein 1.0≤x≤1.08, 0.92≤a<1.0, 0<b≤0.08, 0.005≤c≤0.02, 0.005≤d≤0.02, 1.8≤f≤2.2, 0<p<0.005, 0<n≤0.1, wherein X and Z are main doping elements, M is a secondary doping element, and A is a coating element; X is selected from Y 3+ , Zr 4+ , Sr 2+ , Ce 4+ One of the following, Z is selected from Mo 6+ 、Al 3+ , W 6+ M is at least one of Ti, Mg, Sb, Ca, Nb, Co and Ba; A is at least one of Zr, Sr, Ti, Al, B, W, F and Ca, the ionic radius of Z is less than or equal to the high spin radius of the trivalent nickel ion, and the ionic radius of X exceeds the high spin radius of the trivalent nickel ion by more than 11 pm.
[0005] In one embodiment, X is Y 3+ , Z is Mo 6+ ; or X is Zr 4+ , Z is Al 3+ ; or X is Sr 2+ , Z is W 6+ ; or X is Ce 4 + , Z is Al 3+ .
[0006] In one embodiment, the average primary particle diameter of the binary high-nickel single crystal lithium-ion battery positive electrode material is 0.7-1.1 μm.
[0007] In one embodiment, the binary high nickel single crystal lithium ion battery positive electrode material has a specific surface area of 0.8 m 2 / g-1.5m 2 / g.
[0008] Based on the same inventive concept, a method for preparing a binary high-nickel single crystal lithium-ion battery positive electrode material is also provided, comprising: (1) mixing a positive electrode material precursor, a lithium source, a first main dopant, a second main dopant, and a secondary dopant, and then sintering the mixture for the first time in an oxygen atmosphere to obtain a primary sintered material; (2) mixing the primary sintered material and the first coating agent uniformly and then sintering for a second time in an oxygen atmosphere to obtain a secondary sintered material; (3) After the secondary sintered material and the second coating agent are evenly mixed, a third sintering is performed in an oxygen atmosphere to obtain a binary high-nickel single crystal lithium ion battery positive electrode material.
[0009] In one embodiment, the cathode material precursor D50 is 1.0 μm-2.5 μm.
[0010] In one embodiment, the lithium source is selected from one or more of lithium hydroxide, lithium carbonate, and lithium acetate. In one embodiment, the first sintering is as follows: firstly, the temperature is raised to 400°C~600°C for the first sintering, and the first sintering insulation time is 2h~8h; then, the temperature is raised to 600°C~800°C for the second sintering, and the second sintering insulation time is 8h~25h; finally, the temperature is lowered to 500°C~750°C for the third sintering, and the third sintering insulation time is 2h~15h. In one embodiment, the first coating agent and the second coating agent are both selected from compounds containing one or more of Zr, Sr, Ti, Al, B, W, F, and Ca, and the amount of the first coating agent does not exceed 5% of the molar amount of the primary sintering material, and the amount of the second coating agent does not exceed 2% of the molar amount of the secondary sintering material.
[0011] Based on the same inventive concept, an application is also provided, in which the above-mentioned binary high-nickel single crystal lithium-ion battery positive electrode material is applied in a lithium-ion battery.
[0012] Compared with the prior art, the beneficial effects of the present invention are as follows: It has been found through research that the dual main element and auxiliary element doping of the present invention, wherein the doping amount of the dual main element is much greater than the doping amount of the auxiliary doping element, shows excellent effects in binary single crystals, and can effectively improve the high temperature cycle performance of the positive electrode material without reducing the capacity. However, the same modification method cannot produce the corresponding effect when applied to NCM ternary materials. This is because the elements in the dual main elements whose ion radius is close to that of Ni ions are easy to induce Mn ion reduction but not Ni ion reduction, which will lead to an increase in the energy barrier for Li ion migration, causing serious attenuation of high temperature cycles, and the capacity cannot be guaranteed if the high temperature cycle performance is to be improved. The present application adopts the three-element doping of dual main elements and auxiliary elements in NC single crystals to become quaternary single crystals. The ion radius of the main doping element Z is less than or equal to the high spin radius of the trivalent nickel ion, and the ion radius of the main doping element X is greater than 11pm of the high spin radius of the trivalent nickel ion. The Z ion radius is close to that of nickel ions, and it is easy to induce Ni reduction during discharge, thereby reducing the energy barrier for Li ion migration and improving the cycle performance. The X ion radius is larger than that of nickel ions, and the metal oxygen bond is stronger, which reduces the generation of oxygen vacancies. The reduction of oxygen vacancies will reduce the entry of nickel ions into the lithium layer, thereby improving the nickel dissolution phenomenon in NC binary single crystals. In addition, the dual main doping elements have strong covalent and ionic bonds with oxygen ions, providing an electron to the oxygen ions, stabilizing the valence state of the oxygen ions at -2. This is because the X ion radius is larger than that of nickel and cobalt ions, and provides electron pairs to oxygen ions through covalent bonding, stabilizing the valence state of oxygen ions, and preventing them from participating in oxidation-reduction during the charge and discharge process, thereby minimizing oxygen release, which can greatly improve high-temperature cycle performance. In addition, the above-mentioned positive electrode material uses a three-element doping of dual main elements and a secondary element to ensure that it maintains good high-temperature cycle performance while not reducing the capacity of the positive electrode material. First, because the Z ions induce Ni reduction during discharge, the migration energy barrier of Li is reduced, while improving the cycle, the polarization of the first discharge is also smaller, allowing more Li ions to be embedded faster, and still maintaining high capacity performance. Secondly, dual main element doping prevents oxygen release, making the surface structure more complete. While the doping elements with large and small ion radii stabilize the structure, the doping element with large ion radius widens the lithium transmission channel and greatly reduces the loss of lithium ion reinsertion, allowing it to maintain high capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0014] Figure 1 This is a SEM image of the binary high-nickel single crystal lithium-ion battery positive electrode material prepared in Example 1 of the present invention; Figure 2a and Figure 2b This is a high temperature cycle performance diagram of the binary high nickel single crystal lithium ion battery positive electrode material prepared in Example 1 of the present invention; Figure 3a and Figure 3b This is a high temperature cycle performance diagram of the binary high nickel single crystal lithium ion battery positive electrode material prepared in Example 2 of the present invention; Figure 4a and Figure 4b This is a high temperature cycle performance diagram of the binary high nickel single crystal lithium ion battery positive electrode material prepared in this comparative example 1; Figure 5a and Figure 5b This is a high temperature cycle performance diagram of the binary high nickel single crystal lithium ion battery positive electrode material prepared in this comparative example 2; Figure 6a and Figure 6b This is a high temperature cycle performance diagram of the binary high nickel single crystal lithium ion battery positive electrode material prepared in this comparative example 3. DETAILED DESCRIPTION
[0015] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0016] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0017] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0018] See also Figure 1 -6, a binary high nickel single crystal lithium ion battery positive electrode material according to an embodiment of the present invention, the general chemical formula of which is Li x Ni a Co b X c Z d M p A n O f , wherein 1.0≤x≤1.08, 0.92≤a<1.0, 0<b≤0.08, 0.005≤c≤0.02, 0.005≤d≤0.02, 1.8≤f≤2.2, 0<p<0.005, 0<n≤0.1, wherein X and Z are main doping elements, M is a secondary doping element, and A is a coating element. X is selected from Y 3+ , Zr 4+, Sr 2+ , Ce 4+ One of the following, Z is selected from Mo 6+ 、Al 3+ , W 6+ M is at least one of Ti, Mg, Sb, Ca, Nb, Co and Ba; A is at least one of Zr, Sr, Ti, Al, B, W, F and Ca, the ionic radius of Z is less than or equal to the high spin radius of the trivalent nickel ion, and the ionic radius of X exceeds the high spin radius of the trivalent nickel ion by more than 11 pm.
[0019] X and Z are main doping elements, the ion radius of Z is less than or equal to the high spin radius of trivalent nickel ions, and the ion radius of X exceeds the high spin radius of trivalent nickel ions by more than 11 pm.
[0020] Preferably, X is Y 3+ , Z is Mo 6+ ; or X is Zr 4+ , Z is Al 3+ ; or X is Sr 2+ , Z is W 6+ ; or X is Ce 4+ , Z is Al 3+, The dual main doping elements are matched in the above manner, and the binary high nickel single crystal lithium ion battery positive electrode material obtained by the above matching manner has better high temperature cycle performance. Among them, the more preferred combination is that X is Y 3+ , Z is Mo 6+ .Mo 6+ can better reduce Ni ions, while Y 3+ It can better stabilize the oxygen element, and the combination of the two can make the high-temperature cycle performance of the binary single crystal better.
[0021] Specifically, in one embodiment, the average primary particle diameter of the binary high nickel single crystal lithium ion battery positive electrode material is 0.7-1.1 μm. The specific surface area of the binary high nickel single crystal lithium ion battery positive electrode material is 0.8 m 2 / g-1.5m 2 / g. The average primary particle diameter is in the range of 0.7-1.1μm. Its small particle size greatly enhances the kinetic performance and shortens the lithium ion transmission distance. The material has enough Li vacancies for lithium ions to smoothly embed back at the end of discharge, thus having higher initial efficiency and capacity performance than traditional single crystals. Specific surface area 0.8m 2 / g-1.5m 2 / g, the large specific surface area can improve the electrochemical activity of the electrode, increase the contact area between the electrode and the electrolyte, and thus improve the discharge capacity. And the large surface area is conducive to improving the dispersion and surface uniformity of the electrode material, thereby improving the stability of a single charge and discharge cycle and the cycle life of the battery.
[0022] Based on the same inventive concept, a method for preparing a binary high-nickel single crystal lithium-ion battery positive electrode material is also provided, comprising the steps of: (1) A positive electrode material precursor, a lithium source, a first main dopant, a second main dopant, and a secondary dopant are mixed and then sintered for the first time in an oxygen atmosphere to obtain a primary sintered material.
[0023] Specifically, the D50 of the positive electrode material precursor is 1.0 μm-2.5 μm. The particle size of the positive electrode material precursor is measured using a Malvern 3000 instrument.
[0024] The lithium source is selected from one or more of lithium hydroxide, lithium carbonate, and lithium acetate. The first main dopant, the second main dopant, and the secondary dopant can be oxides, hydroxides, or organic compounds containing corresponding elements. X is selected from Y 3+ , Zr 4+ , Sr 2+ , Ce 4+ One of the following, Z is selected from Mo 6+ 、Al 3+ , W 6+ M is at least one of Ti, Mg, Sb, Ca, Nb, Co and Ba; A is at least one of Zr, Sr, Ti, Al, B, W, F and Ca, the ionic radius of Z is less than or equal to the high spin radius of the trivalent nickel ion, and the ionic radius of X exceeds the high spin radius of the trivalent nickel ion by more than 11 pm.
[0025] (2) After the primary sintered material and the first coating agent are uniformly mixed, the mixture is subjected to a second sintering in an oxygen atmosphere to obtain a secondary sintered material.
[0026] The first sintering is as follows: firstly, the temperature is raised to 400°C-600°C for the first stage of sintering, the first stage of sintering is kept warm for 2h-8h, then the temperature is raised to 600°C-800°C for the second stage of sintering, the second stage of sintering is kept warm for 8h-25h, and finally, the temperature is lowered to 500°C-750°C for the third stage of sintering, the third stage of sintering is kept warm for 2h-15h.
[0027] In the above step (2), a three-stage sintering process is adopted. In the first and second stages of sintering, lithium ions are completely diffused into the material to form crystals. In the third stage of sintering, the crystals shrink and the stress between the crystals is increased, so that the single crystal particles are completely separated and not adhered. The sintering temperature of the third stage is lower than that of the second stage, which can make the residual lithium salt on the surface of the material fully enter the crystal lattice again during the sintering process, improve the utilization rate of Li ions, reduce the generation of residual lithium on the surface after the first sintering, and the surface area of the highly dispersed and low residual lithium single crystals is higher, the lithium ion reinsertion paths are more, and the subsequent coating is more uniform, thereby showing higher cycle performance.
[0028] (3) After the secondary sintered material and the second coating agent are evenly mixed, a third sintering is performed in an oxygen atmosphere to obtain a binary high-nickel single crystal lithium ion battery positive electrode material.
[0029] The first coating agent and the second coating agent are both selected from one or more oxides, hydroxides or organic compounds containing Zr, Sr, Ti, Al, B, W, F, Ca, etc. The amount of the first coating agent does not exceed 5% of the molar amount of the primary sintering material, and the amount of the second coating agent does not exceed 2% of the molar amount of the secondary sintering material.
[0030] The above binary high-nickel single crystal lithium-ion battery positive electrode material can be used in lithium-ion batteries.
[0031] The "average primary particle diameter" in the following examples and comparative examples is obtained by measuring the maximum diameter of all intact visible primary particles in the 10,000x SEM scanning electron microscope image using Nano measure software, and then calculating the average of the measured values. The above "intact visible" refers to the maximum diameter of the primary particle that can be accurately measured through the electron microscope image.
[0032] In the following examples and comparative examples, the specific surface area of the small-particle quaternary single crystal cathode material prepared in each example and comparative example was measured by BET tester and nitrogen low-temperature adsorption method; the small-particle quaternary single crystal cathode material prepared in each example and comparative example was measured by SEM. The average particle size of the precursor was tested by Malvern 3000.
[0033] Example 1 A binary high nickel single crystal lithium ion battery positive electrode material based on the present invention, comprising Y 3+ 、Mo 6+ As the main doping element, Ba as the secondary doping element, Sr as the first coating element, B and Al as the second coating element, the molecular formula of the positive electrode material is Li 1.06 Ni 0.96 Co 0.02 Y 0.01 Mo 0.01 Ba 0.0006 Sr 0.007 B 0.0073 Al 0.0005 O 2 .
[0034] The method for preparing the binary high-nickel single crystal lithium-ion battery positive electrode material of this embodiment comprises the following steps: (1) Add 0.005% Y to the hydroxide precursor with a Ni-Co ratio of 98:2 2 O 3 With 0.01%MoO3 , mixed with lithium hydroxide in a molar ratio of Li:(Ni+Co+Y+Mo)=1.06, and added BaCO accounting for 0.0006% of the molar content of the precursor 3 Mix well until there are no white spots; (2) placing the mixed material obtained in step (1) in a sintering furnace for the first sintering, first heating the temperature to 500°C for the first sintering, the first sintering heat preservation time is 4 hours, then heating the temperature to 710°C for the second sintering, the second sintering heat preservation time is 12 hours, and finally cooling the temperature to 680°C for the third sintering, the third sintering heat preservation time is 6 hours, cooling after sintering and sieving to obtain a primary sintered material; (3) The primary sintered material and SrCO 3 The mixture is mixed at a molar ratio of 1:0.007, and after being evenly mixed, a second sintering is performed at a sintering temperature of 600° C. and the temperature is kept for 8 hours to obtain a secondary sintered material; (4) The secondary sintered material is mixed with H which accounts for 0.73% of the molar content of the secondary sintered material. 3 BO 3 , 0.00025% Al 2 O 3 After mixing, the third sintering was carried out at a sintering temperature of 300°C and a sintering holding time of 8 hours to obtain a binary high-nickel single crystal lithium-ion battery positive electrode material. The average primary particle diameter was 0.89 μm and the specific surface area was 1.213 m 2 / g, the high temperature cycle capacity retention rate is 92.4%. Figure 1 The high temperature cycle performance diagram is shown in Figure 2a and 2b shown.
[0035] Example 2 A binary high nickel single crystal lithium ion battery positive electrode material based on the present invention, comprising Ce 3+ 、Al 3+ As the main doping element, Ba as the secondary doping element, Sr as the first coating element, B and Al as the second coating element, the molecular formula of the positive electrode material is Li 1.06 Ni 0.97 Co 0.02 Ce 0.005 Al 0.005 Ba 0.0006 Sr 0.007 B 0.0073 Al 0.0005 O 2 .
[0036] The method for preparing the binary high-nickel single crystal lithium-ion battery positive electrode material of this embodiment comprises the following steps: (1) Add 0.005% CeO to the hydroxide precursor with a Ni-Co ratio of 98:2. 2 With 0.0025%Al 2 O 3 , mixed with lithium hydroxide according to the molar ratio of Li:(Ni+Co+Ce+Al)=1.06, and added BaCO accounting for 0.0006% of the molar content of the precursor 3 Mix well until there are no white spots; (2) placing the mixed material obtained in step (1) in a sintering furnace for the first sintering, first heating to 400°C for the first stage of sintering, the first stage of sintering and heat preservation time is 4 hours, then heating to 650°C for the second stage of sintering, the second stage of sintering and heat preservation time is 12 hours, and finally cooling to 620°C for the third stage of sintering, the third stage of sintering and heat preservation time is 6 hours, cooling after sintering and sieving to obtain a primary sintered material; (3) The primary sintered material and SrCO 3 The mixture is mixed at a molar ratio of 1:0.007, and after being evenly mixed, a second sintering is performed at a sintering temperature of 600° C. and the temperature is kept for 8 hours to obtain a secondary sintered material; (4) The secondary sintered material is mixed with H which accounts for 0.73% of the molar content of the secondary sintered material. 3 BO 3 , 0.00025% Al 2 O 3 After mixing, the third sintering was carried out at a sintering temperature of 300°C and a sintering holding time of 8 hours to obtain a binary high-nickel single crystal lithium-ion battery positive electrode material. The average primary particle diameter was 0.91 μm and the specific surface area was 1.143 m 2 / g, and the high temperature cycle capacity retention rate is 91.8%. Figure 3a and 3b shown.
[0037] Example 3 A binary high nickel single crystal lithium ion battery positive electrode material based on the present invention, comprising Zr 4+ 、Al 3+ As the main doping element, Ba as the secondary doping element, Sr as the first coating element, B and Al as the second coating element, the molecular formula of the positive electrode material is Li 1.06 Ni 0.94 Co 0.02 Zr 0.02 Al 0.02 Ba 0.0006 Sr 0.007 B 0.0073 Al 0.0005 O 2 .
[0038] The method for preparing the binary high-nickel single crystal lithium-ion battery positive electrode material of this embodiment comprises the following steps: (1) Add 0.02% ZrO to the hydroxide precursor with a Ni-Co ratio of 98:2 2 With 0.01%Al 2 O 3 , mixed with lithium hydroxide according to the molar ratio of Li:(Ni+Co+Ce+Al)=1.06, and added BaCO accounting for 0.0006% of the molar content of the precursor 3 Mix well until there are no white spots; (2) placing the mixed material obtained in step (1) in a sintering furnace for the first sintering, first heating the temperature to 550°C for the first sintering, the first sintering heat preservation time is 4 hours, then heating the temperature to 750°C for the second sintering, the second sintering heat preservation time is 12 hours, and finally cooling the temperature to 720°C for the third sintering, the third sintering heat preservation time is 6 hours, cooling after sintering and sieving to obtain a primary sintered material; (3) The primary sintered material and SrCO 3 The mixture is mixed at a molar ratio of 1:0.007, and after being evenly mixed, a second sintering is performed at a sintering temperature of 600° C. and the temperature is kept for 8 hours to obtain a secondary sintered material; (4) The secondary sintered material is mixed with H which accounts for 0.73% of the molar content of the secondary sintered material. 3 BO 3 , 0.00025% Al 2 O 3 After mixing, the third sintering was carried out at a sintering temperature of 300°C and a sintering holding time of 8 hours to obtain a binary high-nickel single crystal lithium-ion battery positive electrode material. The average primary particle diameter was 0.94 μm and the specific surface area was 1.054 m 2 / g, and the high temperature cycle capacity retention rate is 92.0%.
[0039] Comparative Example 1 Compared with Example 1, Comparative Example 1 does not have a main doping element, and the other experimental conditions are consistent with those of Example 1.
[0040] A binary high-nickel single crystal lithium-ion battery positive electrode material for comparison, Ba is used as a doping element, Sr is used as a first coating element, B and Al are used as second coating elements, and the molecular formula of the positive electrode material is Li 1.06 Ni 0.98 Co 0.02 Ba 0.0006 Sr 0.00 7 B 0.0073 Al 0.0005 O 2 .
[0041] The average primary particle diameter of the obtained binary high-nickel single crystal lithium-ion battery positive electrode material is 0.87 μm and the specific surface area is 1.386 m 2 / g, and the high temperature cycle capacity retention rate is 83.8%. Figure 4a and 4b shown.
[0042] Comparative Example 2 Compared with Example 1, in Comparative Example 2, the main doping element is Y, a single main element is doped with a secondary element, and the other experimental conditions are consistent with Example 1.
[0043] A binary high-nickel single crystal lithium-ion battery positive electrode material for comparison, Y as the main doping element, Ba as the secondary doping element, Sr as the first coating element, B and Al as the second coating element, the positive electrode material has a molecular formula of Li 1.06 Ni 0.97 Co 0.02 Y 0.01 Ba 0.0006 Sr 0.007 B 0.0073 Al 0.0005 O 2 .
[0044] The average primary particle diameter of the obtained binary high-nickel single crystal lithium-ion battery positive electrode material is 0.88 μm and the specific surface area is 1.245 m 2 / g, the high temperature cycle capacity retention rate is 86.0%, and the high temperature cycle performance is shown in the figure Figure 5a and 5b shown.
[0045] Comparative Example 3 Compared with Example 1, in Comparative Example 3, the main doping element is Mo, and a single main element and a secondary element are doped. The other experimental conditions are consistent with those of Example 1.
[0046] A binary high-nickel single crystal lithium-ion battery positive electrode material for comparison, Mo as the main doping element, Ba as the secondary doping element, Sr as the first coating element, B and Al as the second coating element, the molecular formula of the positive electrode material is Li 1.06 Ni 0.97 Co 0.02 Mo 0.01 Ba 0.0006 Sr 0.007 B 0.0073 Al 0.0005 O 2 .
[0047] The average primary particle diameter of the obtained binary high-nickel single crystal lithium-ion battery positive electrode material is 0.89 μm and the specific surface area is 1.213 m 2 / g, and the high temperature cycle capacity retention rate is 85.4%. Figure 6a and 6b shown.
[0048] Performance testing methods The positive electrode material obtained in the embodiment or comparative example is mixed evenly with the conductive agent SP and the binder (PVDF) in a ratio of 92.5:5:2.5, and an appropriate amount of NMP (N-methylpyrrolidone) solution is measured with a pipette as a solvent and added to the above mixed powder material, stirred and coated, and dried at 80°C in a blast drying oven to assemble into a CR2032 button battery. The button battery solvent formula is: EC / DMC=1 / 2 (vol%), 1M LiPF6, VC 1.5wt%, PS 0.5%, EC is ethylene carbonate, DMC is dimethyl carbonate, VC is vinylene carbonate, and PS is sulfite. After packaging, let it stand for 12 hours, and place the button battery that has completed the static infiltration on the blue battery test system for electrochemical performance testing. The high-temperature cycle test method is to cycle 50 times in a constant temperature environment of 45°C, between a voltage of 2.8V-4.3V, with a charge of 0.5C and a discharge of 0.5C.
[0049] According to the high temperature cycle performance of the positive electrode materials obtained in the above embodiments and comparative examples, it can be seen that the binary high nickel single crystal lithium ion battery positive electrode material of the present application is in a constant temperature environment of 45°C, at a voltage between 2.8V-4.3V, and after 50 cycles in a 0.5C charging and 0.5C discharging mode, the high temperature cycle capacity retention rate is 91.8-93%, and the cycle capacity is higher than 213mAh / g. The binary high nickel single crystal lithium ion battery positive electrode material of the comparative example is in a constant temperature environment of 45°C, at a voltage between 2.8V-4.3V, and after 50 cycles in a 0.5C charging and 0.5C discharging mode, the high temperature cycle capacity retention rate is 83.8%-86%, and the cycle capacity is less than 203mAh / g. The high temperature cycle performance of the binary high nickel single crystal lithium ion battery positive electrode material of the present application is significantly higher than the high temperature cycle performance of the comparative example.
Claims
1. A binary high-nickel single crystal lithium-ion battery positive electrode material, characterized in that: Its chemical formula is Li x Ni a Co b X c Z d M p A n O f , wherein 1.0≤x≤1.08, 0.92≤a<1.0, 0<b≤0.08, 0.005≤c≤0.02, 0.005≤d≤0.02, 1.8≤f≤2.2, 0<p<0.005, 0<n≤0.1, wherein X and Z are main doping elements, M is a secondary doping element, and A is a coating element; X is selected from Y 3+ , Zr 4+ , Sr 2+ 、 Ce 4+ One of the following, Z is selected from Mo 6+ 、Al 3+ , W 6+ M is at least one of Ti, Mg, Sb, Ca, Nb, Co and Ba; A is at least one of Zr, Sr, Ti, Al, B, W, F and Ca, the ionic radius of Z is less than or equal to the high spin radius of the trivalent nickel ion, and the ionic radius of X exceeds the high spin radius of the trivalent nickel ion by more than 11 pm.
2. The binary high-nickel single crystal lithium-ion battery positive electrode material according to claim 1, characterized in that: X is Y 3+ , Z is Mo 6+ ; or X is Zr 4+ , Z is Al 3+ ; or X is Sr 2+ , Z is W 6+ ; or X is Ce 4+ , Z is Al 3+ .
3. The binary high-nickel single crystal lithium-ion battery positive electrode material according to claim 1, characterized in that: The average primary particle diameter of the binary high-nickel single crystal lithium ion battery positive electrode material is 0.7-1.1 μm.
4. The binary high-nickel single crystal lithium-ion battery positive electrode material according to claim 1, characterized in that: The specific surface area of the binary high-nickel single crystal lithium-ion battery positive electrode material is 0.8m 2 / g-1.5m 2 / g.
5. The method for preparing the binary high-nickel single crystal lithium ion battery positive electrode material according to any one of claims 1 to 4, characterized in that: Includes steps: (1) mixing a positive electrode material precursor, a lithium source, a first main dopant, a second main dopant, and a secondary dopant, and then sintering the mixture for the first time in an oxygen atmosphere to obtain a primary sintered material; (2) mixing the primary sintered material and the first coating agent uniformly and then sintering for a second time in an oxygen atmosphere to obtain a secondary sintered material; (3) After the secondary sintered material and the second coating agent are evenly mixed, a third sintering is performed in an oxygen atmosphere to obtain a binary high-nickel single crystal lithium ion battery positive electrode material.
6. The preparation method according to claim 5, characterized in that: The cathode material precursor D50 is 1.0 μm-2.5 μm.
7. The preparation method according to claim 5, characterized in that: The lithium source is selected from one or more of lithium hydroxide, lithium carbonate and lithium acetate.
8. The preparation method according to claim 5, characterized in that: The first sintering is as follows: firstly, the temperature is raised to 400°C-600°C for the first stage of sintering, the first stage of sintering is kept warm for 2h-8h, then the temperature is raised to 600°C-800°C for the second stage of sintering, the second stage of sintering is kept warm for 8h-25h, and finally, the temperature is lowered to 500°C-750°C for the third stage of sintering, the third stage of sintering is kept warm for 2h-15h.
9. The preparation method according to claim 5, characterized in that: The first coating agent and the second coating agent are both selected from one or more compounds containing Zr, Sr, Ti, Al, B, W, F, and Ca. The amount of the first coating agent does not exceed 5% of the molar amount of the primary sintering material, and the amount of the second coating agent does not exceed 2% of the molar amount of the secondary sintering material.
10. Use of the binary high-nickel single crystal lithium-ion battery positive electrode material according to any one of claims 1 to 4 in a lithium-ion battery.
Citation Information
Patent Citations
A binary high-nickel single-crystal cathode material and its preparation method
CN114068912B